Translation Challenges Among English-Majored Students: A Case Study at Thu Dau Mot University - Nguyen Van, Hung (Technium Social Sciences Journal, 2025)
Translation is a compulsory subject in Thu Dau Mot University’s English Language curriculum and is considered the most difficult subject of all the language skills, requiring students to have extensive knowledge of vocabulary, grammar and sentence structure. In fact, Thu Dau Mot University’s English-majored students face many challenges in the process of practicing English - Vietnamese and Vietnamese - English translation. The article points out the factors affecting students' development of translation skills and suggests some effective ways to help students improve their translation skills. The survey was conducted with the participation of 108 fourth-year English majors at Thu Dau Mot University. The results show that most students have difficulties with vocabulary, grammar and structure due to the differences in the two languages.